KEUANGAN DIGITAL UNTUK KEBERLANJUTAN: PENGARUH E-WALLET, DIGITAL PAYMENT, DAN LITERASI DIGITAL TERHADAP PENGGUNAAN KERTAS - I Gusti Ayu Nindia Sri Pramesti; Gusi Putu Lestara Permana (Universitas Prof.Hazairin,SH Bengkulu, 2025)
The swift progress of financial technology has reshaped everyday activites, especially in financial transactions that are moving toward to electronic platforms. This research investigates to examine how the adoption of e-wallet, digital payment, and digital literacy on reducing paper usage in Denpasar City. Using a quantitative method with purposive sampling, the study surveyed 120 respondents who regularly engage in financial technology. Questionnaire data were analyzed through multiple linear regression. The outcomes show that e-wallet adoption, digital payment, and digital literacy each exert a significant negative influence on paper consumption. This suggests that broader financial technology adoption and stronger digital literacy decrease reliance on printed documents. Moreover, the analysis indicates that 63.4% of the variation in paper usage can be attributed to the three independents variables, underlining the crucial role of digital transformation in promoting environmental sustainability.